Utilisation of phosphogypsum along with other additives in geo- engineering- A review - B. Anamika; G. Debabrata (Materiales de Construccion, 2022)
Various adverse effects and hydro-mechanical failures of soil are the dominant effects of global warming. At the same time, rapid industrial development has produced several by-products on a large scale. The reuse of industrial residues in different engineering fields without compromising the technical characteristics is propitious from the engineering, environmental, ecological and economic points of view. Phosphogypsum (PG) can be used as an alternative civil engineering material as it is rich in calcium sulphate, although it contains some radioactive molecules. Researchers are continuing to investigate the utilisation of PG by mixing it with other traditional materials to convert into alternative materials when the radioactive minerals are within the permissible limits. However, the contamination effect can be reduced by treating with citric acid. This review paper presents details of the increase in strength parameters and permeability of PG when combined with other wastes materials used in different geotechnical fields.